Event tree algorithms to generate test sequences for composite Web services. (7th June 2017) - Endo, Andre Takeshi; Simao, Adenilso
Summary: In service‐oriented architecture testing, the behaviour of a composite service and its partner services can be represented as an event graph (model). As test cases are derived from such a model, the Chinese postman problem (CPP) algorithm is applied to cover all edges. Although CPP provides an optimal solution, there is a lack of alternative algorithms to obtain not only a faster execution but also a satisfactory solution. This paper introduces the event tree algorithm (ETA) to generate test cases from event sequence models for Web service compositions. Two strategies are also proposed to improve ETA: First, a greedy strategy to build the tree is defined based on the cost of expanding given edges. Second, redundant elements are eliminated (pruned) in the tree. Four versions of ETA are compared with CPP with respect to test suite size, generation time, number of test sequences, and test sequence length. Abstract : We introduce 4 versions of an event tree algorithm to generate test sequences for composite services. When compared with Chinese postman problem (CPP), the proposed algorithms were faster, though CPP generated smaller test suites. For real‐world models, the best version of event tree algorithm (which adopts greedy and pruning strategies) generates test suites with the same size of CPP.